Differential exposure to palatable food and its effects on binge-like eating behavior in adolescent rats - Chávez-Hernández, María Elena; Rodríguez-Serrano, Luis Miguel; Díaz-Urbina, Daniel; Muñóz-Sánchez, Sinuhé; Buenrostro-Jáuregui, Mario Humberto; Escartín-Pérez, Rodrigo Erick (Frontiers in Psychology, 2024)
Introduction. Consumption of palatable food (PF) can lead to chronic overconsumption and obesity. Furthermore, adolescents may be vulnerable to excessively reinforcing foods, which increases the probability of developing overweight and obesity in adulthood. The role of PF availability in binge-like intake among adolescents without caloric needs remains unclear. The present study aimed to evaluate which PF access protocol is the most sensitive to induce increased caloric intake and binge-like eating during adolescence. Methods. We used twenty-four male Wistar rats (30 postnatal days [PND]); standard food and water were provided ad libitum. Rats were randomly assigned to one of three groups: a) continuous, daily access to PF; b) intermittent, 1-day access/1-day no-access; or c) weekend, 3 daysaccess/4 days no-access. All groups had 1h access to PF (chocolate sandwich cookies). Access protocols were maintained for 6 weeks; afterward, rats underwent a 7-day withdrawal period, and were then evaluated on a binge-eating test. Results. Chronic restricted PF access induces binge-like intake, with intermittent access resulting in the highest binge index. Additionally, caloric intake of PF increases over time during adolescence, with differential effects of intermittent and weekend access. Conclusion. Chronic restricted access to PF during adolescence induces binge-like intake, with differences depending on PF availability. This can lead to chronic overconsumption under non-homeostatic conditions.